Sulforaphane protects against LPS-induced liver injury in mice by antagonizing oxidative stress and apoptosis through AMPK activation - Mansouri, Rasha; Alshaibi, Huda; Alqurashi, May M.; Shaikh, Maimoonah; Bahaidrah, Khulud; Alzahrani, Noor (International Journal of Health Sciences, 2024)
Objectives: Given the adverse effect of liver injury on a multitude of body functions, it is vital to understand its underlying mechanism and how to overcome it. In this study, lipopolysaccharide (LPS) was used to induce liver injury, while sulforaphane (SFN), a natural phytochemical, was used as the antagonist to overcome the deleterious effect. Methods: Twenty-four mice were divided into three groups: Control group (0.9% saline), LPS induction group (0.75 mg/kg), and SFN treatment (25 mg/kg) followed by LPS induction group (0.75 mg/kg), all with access to food and water ad libitum. Blood samples from retro-orbital sinus were used to measure liver function through two aminotransferases (i.e., alanine transaminase [ALT] and aspartate transaminase [AST]) whereas liver homogenate was used to measure glutathione (GSH), catalase (CAT), and superoxide dismutase (SOD) (antioxidant activity markers); caspase-3 (apoptosis marker); malondialdehyde (MDA) (lipid peroxidation marker); and NO. AMP-activated protein kinase (AMPK), a cellular energy homeostasis and lipid metabolism sensor, was also measured. Statistical analysis including normalization, analysis of variance, Kruskal–Wallis test, and significance of P < 0.05 were applied to all collected data. Results: SFN treatment significantly attenuated all tests compared to the induced liver injury by LPS where significant reduction was observed in the levels of hepatic function markers (AST and ALT), lipid peroxidation marker (MDA) as well as apoptosis marker (caspase-3) whereas a marked increase was observed for antioxidant activity markers (SOD, CAT, and GSH) and AMPK. Conclusion: These results indicate the protective effect of SFN as it re-instated the levels of antioxidation while decreasing the level of the biomarkers, which were significantly increased during liver injury induction by LPS.